Second species of unusual leafhopper genus Univagris (Hemiptera: Cicadellidae: Deltocephalinae) from India - Rajgopal, N. N.; Meshram, Naresh M. (Zootaxa, 2018)
A new leafhopper species, Univagris tenebra sp. nov., is described and illustrated from India (Himachal Pradesh: Banjar). Detailed photographic illustrations, an annotated checklist and key to the species along with photographic illustrations for Univagris pallida Virakthamath & Murthy are provided.